Effects of multifaceted street art on price premium of pre war commercial buildings: the case of Georgetown UNESCO world heritage site - Cheng, Chin Tiong (MDPI, 2023)
Street art is promoted in most countries to intensify the cultural elements of the cityscape. Although street art provides cultural and social values, its impact on the prices of prewar historic property is still unknown. Therefore, an empirical study that examines the relationship between prewar shophouse prices and street art is needed to improve real estate professionals’ understanding of the historic preservation market. Using pre- and post-models for the years 2009 to 2019, this study systematically determined the actual location of 119 street art objects (in the form of sculptures and murals) and the 852 prewar shophouses sold in George Town, Penang. The price change of prewar shophouses correlates with the number of street art objects within 100 m, 500 m, and 1000 m of the properties. Due to the heterogeneous characteristics of the properties, six primary hedonic models were developed to extract the price premium of street art. This study has shown the impact of street art on a prewar commercial building, where an additional unit of sculpture could increase its price by 8.32%, 1.62%, and 0.74%, based on radii of 100 m, 500 m, and 1000 m, respectively, in the post-model (after 2012–2019). However, a mural painting has no significant effect on the price change of prewar shophouses. In addition, the position of street art (representing visibility) in the model was tested. The result shows that, unlike sculptures that were located at the back of prewar houses, such street art effects contributed positively to the price premium when they were located at the front of the buildings, with each additional unit of sculpture increasing the price premium of prewar houses by 1.13%. Sculptures as street art thus created a positive externality for the city, particularly with respect to the price premium for prewar shophouses.